PENINGKATAN BUDAYA LITERASI MELALUI MEDIA VISUAL DI KALANGAN ANAK, REMAJA, DAN DEWASA DI KECAMATAN WONOKERTO - Reny Wiyatasari (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
This service’s activity to society aims to find out the interest and literacy abilities of elementary, junior high and junior high school youth in Wonokerto subdistrict, methods that can be applied to improve the culture of young generation literacy in Wonokerto Subdistrict, and obstacles that cause low literacy culture in Wonokerto Subdistrict. Service’s activity to societyactivities aimed to improving literacy culture were carried out in four villages in Wonokerto District for seven weeks. In the first week of observation, situation analysis and action determination; in the second week preparing a proposal and submitting a permit; in the third week until the sixth week, socializing, training and evaluating; and in the seventh week compiling reports and devotion articles. The results of dedication activities based on evaluation are known that the object / target literacy ability, especially at the informational and epistemic levels, significantly increasesKeywords:literacy skills, visual media, short story, poem